Kedudukan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2020 Perspektif Ilmu Perundang-Undangan - Tigor Einstein; Muhammad Ishar Helmi; Ahmad Ramzy (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe Covid-19 case puts the world in a state of turmoil, uncertainty, complexity and uncertainty, making problems, challenges, and even threats of the Indonesian nation and state increasingly large and complex. Entering 2020, the entire world including Indonesia is threatened by the outbreak of the spread of Covid-19. As a result of Covid-19, all lives of the Indonesian people, including economic life, are threatened. To remedy this situation, the President established a policy in the form of Government Regulation in Lieu of Law Number 1 Year 2020 concerning State Financial Policy and Financial System Stability for Handling Corona Virus Disease 2019 (Covid-19) and / or In Order to Face Threats that Endanger the National Economy and / or Financial System Stability. This government policy did not go smoothly, but received a lot of criticism from various parties.Keywords: Perppu, legislation AbstrakKasus Covid-19 menjadikan dunia berada dalam keadaan yang bergejolak (Volatility), tidak pasti (Uncertainity), kompleks (Complexity), dan tidak jelas (Ambiguity) membuat persoalan, tantangan, bahkan ancaman bangsa dan negara Indonesia bertambah besar dan kompleks. Memasuki tahun 2020, seluruh dunia termasuk Indonesia terancam dengan merebaknya penyebaran Covid-19. Akibat Covid-19 ini, segala kehidupan bangsa Indonesia, termasuk kehidupan ekonomi menjadi terancam. Untuk memperbaiki keadaan tersebut, Presiden menetapkan kebijakan berupa Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2020 tentang Kebijakan Keuangan Negara dan Stabilitas Sistem Keuangan Untuk Penanganan Pandemi Corona Virus Disease 2019 (Covid-19) dan/atau Dalam Rangka Menghadapi Ancaman Yang Membahayakan Perekonomian Nasional dan/atau Stabilitas Sistem Keuangan. Kebijakan pemerintah ini tidaklah berjalan mulus begitu saja, melainkan mendapat banyak kritik dari berbagai pihak.Kata Kunci: Perppu, Perudang-undangan